Rheo-mechanical, hardened mechanical characterisation, and tensile creep of limestone calcined clay cement fibre-reinforced printed concrete (LC3-FRPC) - Ibrahim, Kamoru Ademola (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.